2019
DOI: 10.1002/ejoc.201900529
|View full text |Cite
|
Sign up to set email alerts
|

Gold(I) Complexes in Ionic Liquids: An Efficient Catalytic System for the C‐H Functionalization of Arenes and Heteroarenes under Mild Conditions

Abstract: Use of ionic liquids bearing the proper counteranion as reaction solvents allows to boost the reactivity of gold(I) complexes as catalysts in the hydroarylation of alkynes with arenes and heteroarenes. Several commercial complexes of general structure LAuX have been tested as catalysts, with L=1,3‐bis(2,6‐diisopropylphenyl)imidazol‐2‐ylidene standing out as the one delivering the best performance. Beside high activity, enabling the use of <1 mol‐% catalyst under mild conditions (low temperature, no need for an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 69 publications
0
19
0
Order By: Relevance
“…From 1 H NMR kinetics, it was confirmed that IPrAuNTf 2 promotes the in situ σ,π‐acetylide formation from terminal alkynes, which enables the reversibility of protons to favor the crucial second hydroarylation. Biffis and Baron recently unraveled a similar sort of double C−H activation of heteroarenes towards alkynes by gold(I) catalysis in ionic liquid ([BMIM][NTf 2 ]) [250] . This chemistry is site‐selective with respect to heteroarenes and regioselective with respect to alkynes.…”
Section: Selective Hydroarylation Of π‐Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
See 1 more Smart Citation
“…From 1 H NMR kinetics, it was confirmed that IPrAuNTf 2 promotes the in situ σ,π‐acetylide formation from terminal alkynes, which enables the reversibility of protons to favor the crucial second hydroarylation. Biffis and Baron recently unraveled a similar sort of double C−H activation of heteroarenes towards alkynes by gold(I) catalysis in ionic liquid ([BMIM][NTf 2 ]) [250] . This chemistry is site‐selective with respect to heteroarenes and regioselective with respect to alkynes.…”
Section: Selective Hydroarylation Of π‐Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
“…Biffis and Baron recently unraveled a similar sort of double CÀ H activation of heteroarenes towards alkynes by gold(I) catalysis in ionic liquid ([BMIM][NTf 2 ]). [250] This chemistry is site-selective with respect to heteroarenes and regioselective with respect to alkynes. Likewise, it is relevant that AuBr 3 also catalyzes the regioselective hydroarylation of phenylacetylene with 2,4,5-trisubstituted furan to afford sequential Markovnikovselective hydrofurylated product.…”
Section: Selective Hydroarylation Of π-Systems By Furans Pyrroles and Thiophenesmentioning
confidence: 99%
“…In comparison, the same group reported that AuCl 3 -catalyzed hydroarylation of the same alkyne by mesitylene requires days and the addition of a silver(I) salt. In our hands [111], Au(I)-catalyzed hydroarylation of ethyl propiolate by heteroarenes in ionic liquids achieves similar conversion at room temperature instead of 60 • C, under otherwise identical conditions. Furthermore, in contrast with hydroarylation with regular arenes (see Section 6.1), hydroarylation of both electron-rich phenylacetylene and electron-deficient ethyl propriolate can be effectively catalyzed by Au(I)-NHC and Au(I)-phosphine complexes.…”
Section: Intermolecular Hydroarylation With Heteroarenesmentioning
confidence: 69%
“…In our most recent contributions to this topic, [110,111] ionic liquids (IL) are adopted as the solvent system in Au(I) catalysis of Reaction 2. Under neutral conditions in an IL, IPrAuCl catalyzed Reaction 2 at low catalyst loading to achieve full conversion of the alkyne within one hour, a significant improvement over the same system in dichloroethane.…”
Section: Hydroarylationmentioning
confidence: 99%
“…Since the turn of the century, homogeneous gold catalysis has become increasingly popular for facilitating chemoselective nucleophilic additions to unsaturated carbon–carbon bonds . For example, the hydroarylation of alkynes with indoles has been studied extensively using gold catalysis due to the products’ relevance in medicinal and natural products. , The intermolecular version of this reaction with unactivated alkynes has previously been reported to occur via double addition of the indole to form symmetrical 3,3′-bis­(indolyl)­methanes (BIMs) 3 (Scheme A). ,, It is usually not possible to isolate the single addition vinylindole intermediates 4 , , as 4 reacts further under these conditions to form BIMs 3 . The BIM motif appears in many natural and pharmaceutically active compounds, such as echinosulfonic acids A–D and mucronatins A and B (Figure ), and synthetic methods toward these motifs have therefore been widely investigated .…”
mentioning
confidence: 99%